2022
DOI: 10.1155/2022/4914151
|View full text |Cite
|
Sign up to set email alerts
|

Research on Efficiency in Financing of Small and Medium Companies Based on DEA Method

Abstract: At this stage, SMEs cannot survive and grow without the support of large amounts of capital, and the issue of financing efficiency has always been a bottleneck for different types of SMEs. This paper studies the financial data of relevant enterprises by constructing variable index evaluation systems such as anti-risk ability, internal management, financial system, market competitiveness, short-term debt, long-term debt, paid-in capital to property right ratio, comprehensive efficiency, pure technical efficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…On the other hand, firms in manufacturing and high-tech industries have increasing returns to scale, and thus, they are more likely to have better results from financial ratios (asset liability, current, liquidity, etc.) that indicate better financial conditions (Pang & Gai, 2022). Moreover, Belas et al (2021) analyze SMEs in V4 countries (Visegrad) and affirm the positive relationship between innovation and the financial risk management of SMEs.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, firms in manufacturing and high-tech industries have increasing returns to scale, and thus, they are more likely to have better results from financial ratios (asset liability, current, liquidity, etc.) that indicate better financial conditions (Pang & Gai, 2022). Moreover, Belas et al (2021) analyze SMEs in V4 countries (Visegrad) and affirm the positive relationship between innovation and the financial risk management of SMEs.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 97%
“…When SMEs make technology investments, they receive more benefits regarding enterprise financing. Innovations that stem from developing novel goods and implementing new technologies also increase SMEs' market share and income (Pang & Gai, 2022). Nwekpa et al (2018) emphasize that innovative firms increase their sales and financial assets more than their less innovative counterparts.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…At present, DEA is widely used in the field of financing efficiency, and it has achieved many important research milestones. Pang and Gai [34] study the financing efficiency of small and medium-sized enterprises based on the DEA method. Jin et al [35] use the DEA method to measure the financing efficiency of listed companies in the energy conservation and environmental protection industry.…”
Section: Index Calculationmentioning
confidence: 99%
“…We extend the model by adding other control variables that may affect the company's financing efficiency, and we control the variables from both the micro enterprise level and macro level perspectives. At the corporate level, we control the size of the enterprise, profitability, revenue growth rate, cash flow level, asset liability ratio, shareholder shareholding, and Tobin Q value, as these variables significantly affect the financing efficiency of the enterprise [34][35][36]. At the macro level, we control the GDP growth rate to eliminate macro level interference.…”
Section: Control Variablementioning
confidence: 99%
“…It is observed that an important part of the problem is that there are many different variables that can be used to measure the performance, profitability, and success of a company [131]. While some papers approach the issue from a purely economic and financial point of view [149], other studies approach it from the point of view of the organisation and management of the company [150,151]. is supports the idea that it is necessary to combine both types of variables, and there are alternative ways for the survival of the companies in the time.…”
Section: Introductionmentioning
confidence: 99%